"For the Gram": An Exploration of the Conflict between Influencers and Citizen-Consumers in the Public Lands Marketing System. (December 2021) - Ray Chaudhury, Sarita; Nafees, Lubna; Perera, B. Yasanthi
Capturing memories is integral to public lands visitors' consumer experiences. Today, social media allows us to share photographs and videos in the public domain, whether it be for instant gratification, economic gain, or both. The phenomenon of sharing public lands digital imagery on social media has created tensions in the public lands marketing system (PLMS) between those wanting to preserve the outdoors and those seeking to monetize it. Using the Instagram account @publiclandshateyou as a case study site, this research utilizes an interpretive "thick data" visual analysis to examine how interlinked marketing systems (e.g., travel, tourism, outdoor recreation), which includes the social media marketing system (SMMS) contribute to this conflict in the PLMS. Findings indicate that citizen-consumer oriented practices, rooted in "sense of place, " attempt to bring change to the interlinked marketing systems.